2008
DOI: 10.1002/mc.20444
|View full text |Cite
|
Sign up to set email alerts
|

ERp29, an endoplasmic reticulum secretion factor is involved in the growth of breast tumor xenografts

Abstract: Cancer cells are committed to an actively secretory state that facilitates communication with their microenvironment. We have addressed the role of ERp29, a novel endoplasmic reticulum secretion factor in mammary carcinogenesis using MCF-7 human breast cancer cells as a model. Xenografts originating from cells stably transfected with dominant-negative form of ERp29 were smaller and better differentiated than those derived from cells overexpressing wild-type ERp29. Similar effects were observed by siRNA-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
0
16
0
2
Order By: Relevance
“…In support of our findings, studies from Shnyder et al 24 showed that cells (MCF-7 and COLO205) with a high level of ERp29 produced slow-growing tumors, whereas cells (MDA-MB-435) with a low level of ERp29 developed fast-growing tumors. Nevertheless, conflicting results have been reported by Mkrtchian et al 25 They found that mutant ERp29C157A inhibited tumor growth as compared with wild-type ERp29, and the size of established tumors could not be further increased when tumors were treated with ERp29 siRNA. Although the reasons of this discrepancy are uncertain, one possible explanation may be that tumor suppression by nonfunctional mutant ERp29C157A is apparently because of the disruption of a secretion pathway, 41 which may affect stromal-tumor cell interaction.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In support of our findings, studies from Shnyder et al 24 showed that cells (MCF-7 and COLO205) with a high level of ERp29 produced slow-growing tumors, whereas cells (MDA-MB-435) with a low level of ERp29 developed fast-growing tumors. Nevertheless, conflicting results have been reported by Mkrtchian et al 25 They found that mutant ERp29C157A inhibited tumor growth as compared with wild-type ERp29, and the size of established tumors could not be further increased when tumors were treated with ERp29 siRNA. Although the reasons of this discrepancy are uncertain, one possible explanation may be that tumor suppression by nonfunctional mutant ERp29C157A is apparently because of the disruption of a secretion pathway, 41 which may affect stromal-tumor cell interaction.…”
Section: Discussionmentioning
confidence: 92%
“…20,21 Importantly, it was found to be highly expressed in primary tumor and cell lines. [22][23][24] Recent findings that ERp29 expression correlated with tumor growth rate 24 and knockdown of ERp29 by siRNA in noninvasive MCF-7 breast cancer cells attenuated tumorigenesis 25 imply an oncogenic role of ERp29 in breast tumor formation. In contrast, Shnyder et al 24 also observed a low level of ERp29 in proliferative and metastatic MDA-MB-435 cells compared with MCF-7 cells, and an inverse correlation between ERp29 expression and tumor progression, although not at a significant level.…”
mentioning
confidence: 99%
“…These results were gained by two alternative methods: transfection of breast cancer cells with a dominant-negative ERp29 variant or ERp29 overexpression as well as gene silencing using siRNA techniques. Xenograft cells with the dominant-negative ERp29 isoform furthermore exhibited a higher differentiation and were smaller, but cell growth in vitro was unchanged as compared to wild type or overexpressing cells (Mkrtchian et al 2008). These findings are in disagreement with those by Bambang et al describing ERp29 as putative tumour suppressor in breast cancer due to its ability to reduce xenograft growth in nude mice, arrest cells at G0/G1 and inhibit cell proliferation (Bambang et al 2009).…”
Section: Discussionmentioning
confidence: 95%
“…It is localised in the endoplasmic reticulum and was primarily described as a chaperone for secretory proteins, including thyroglobulin (Sargsyan et al 2002) and is ubiquitously expressed with brain levels higher as compared to other organs (MacLeod et al 2004). Mkrtchian et al (2008) showed that ERp29 downregulation led to volume reduction in breast cancer xenografts. These results were gained by two alternative methods: transfection of breast cancer cells with a dominant-negative ERp29 variant or ERp29 overexpression as well as gene silencing using siRNA techniques.…”
Section: Discussionmentioning
confidence: 98%
“…Proteins were extracted from cultured A549 cells or MEFs as previously described before [17,18]. Briefly, The cells were lysed at 4°C for 20 min using a lysis buffer (Ripa, Invitrogen and proteinase inhibitor).…”
Section: Western Blot Analysismentioning
confidence: 99%